Cross-School Collaborative Academic Supervision for Integrated Science and Social Studies Teachers: A Qualitative Case Study in Indonesian Madrasahs - Kholidi Kholidi; Muhali Muhali; Lovy Herayanti (Universitas Pendidikan Mandalika, 2026)
This study examined the implementation of cross-school collaborative academic supervision for Integrated Science and Social Studies teachers in Indonesian madrasahs. Using a qualitative instrumental case study design, the research involved six madrasahs, twelve teachers, six principals serving as cross-school supervisors, and two officials from the Working Group of Madrasah Ibtidaiyah (Kelompok Kerja Madrasah Ibtidaiyah - KKMI). Data were collected through semi-structured interviews, non-participant observations, and document analysis, and were analyzed through data condensation, data display, and conclusion verification. The findings showed that the supervision process comprised collective planning, pre-observation conferences, classroom observations, teacher-led reflection, evidence-based feedback, and follow-up planning. Participants perceived the cross-school arrangement as broadening the sources of professional feedback and supporting more participatory reflective dialogue. However, the program did not eliminate the evaluative pressure of supervision, as all teachers reported nervousness during classroom observation. Professional learning needs included interdisciplinary lesson planning, inquiry- and project-oriented instruction, authentic assessment, and the use of instructional resources. Feedback also varied in specificity across madrasah accreditation contexts, indicating the need for differentiated support. The study concludes that cross-school collaborative supervision provides a promising framework for professional learning, but its longer-term contribution depends on sustained mentoring, repeated observation cycles, supervisor preparation, and adequate institutional support.